Safety of Drainless Donor Closure in DIEP Flap-Based Breast Reconstruction: A Prospective Analysis Using Ultrasound - Kim, Jina; Lee, Kyeong-Tae; Mun, Goo-Hyun (Journal of Reconstructive Microsurgery, 2023)
Background Although drainless donor closure with progressive tension suture (PTS) technique has been attempted to further reduce donor morbidity in deep inferior epigastric perforator (DIEP) flap-based breast reconstruction, its clinical safety has not yet been fully elucidated. This study prospectively investigated donor morbidity after DIEP flap elevation and drain-free donor closure.Methods A prospective cohort study was performed on 125 patients who underwent DIEP flap-based breast reconstruction and drainless donor closure. Postoperatively, the donor site was evaluated repetitively using ultrasonography. Development of donor complications, including any fluid accumulation and seroma (defined as detection of fluid accumulation after postoperative one month), was prospectively noted, and independent predictors for the adverse events were evaluated.Results On ultrasound examination conducted within postoperative 2 weeks, 48 patients were detected to have fluid accumulation at the donor site, which were more frequently detected in cases of delayed reconstruction and those with lesser number of PTS conducted. The majority of those events (95.8%) were resolved with one- or two-times ultrasound-guided aspirations. Five patients (4.0%) showed persistent fluid accumulation after postoperative 1 month, which were successfully treated with repetitive aspiration without requiring reoperation. No other abdominal complications developed except for three of delayed wound healing. On multivariable analyses, harvesting larger-sized flap and conducting lesser number of PTS were independent predictors for the development of fluid accumulation.Conclusion The results of this prospective study suggest that drainless donor closure of the DIEP flap with meticulous placement of PTS followed by postoperative ultrasound surveillance appears to be safe and effective.
Keywords: breast reconstruction; DIEP flap; donor closure; progressive tension suture; seroma; ultrasonography